TALENT MANAGEMENT IN HIGHER EDUCATION: A CRITICAL REVIEW - Asma Shughail Aqib Al Hashimi; Adi Anuar Azmin; Mohd Zukime Mat Junoh, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aimed to articulate the critical issues related to talent management (TM). A critical literature review was performed to discuss the significance of TM in universities and its role in aligning higher education with industrial labour requirements. Relevant literature was obtained from an extensive search of human resource journals indexed with Google Scholar, ScienceDirect, EBSCO Information Services, ProQuest, and Emerald Insight databases. The findings revealed that TM supported the competitiveness and learning outcomes in the education sector. Furthermore, this study forwarded a novel conceptual framework for integrating higher education with industrial human capital needs. Based on the results, it is recommended that the integration of TM systems in universities and organisations can ensure the university graduates address the industry needs. Therefore, collaborative planning for talent supply management models in universities and industries is vital for developing academic TM systems that align with the extensive national economic, political, and social systems.